Implementation of the Use of Social Media Through the Shopee Application in Understanding Consumer Behavior to Increase Sales of MSME Products - Riya Rahmadani; Wahyu; Khairin Dinawari Setiawan; Selvia Hernawati; Muhammad Hasan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Study This investigate how MSMEs use social media via Shopee for understand behavior consumers and improve sale product they. With approach qualitative and study case, research This use interview in depth and analysis Shopee social media content as tool data collection. Findings main involve variation experience user in shopping, role interaction consumers on Shopee social media, as well impact positive visual content in influence decision purchase. The result highlighting importance review positive and testimonial consumer in push purchase. Discussion study emphasize experience users, interaction strategies on social media, and their importance visual content for interesting interest consumer